Clinical and functional characteristics of the E92K CFTR gene variant in the Russian and Turkish population of people with cystic fibrosis - KARADAĞ, BÜLENT TANER; GÖKDEMİR, YASEMİN (My University, 2023)
The pathogenic variant E92K (c.274G > A) of the CFTR gene is rare in America and Europe, but it is common for people with cystic fibrosis from Russia and Turkey. We studied the effect of the E92K genetic variant on the CFTR function. The function of the CFTR channel was studied using the intestinal current measurements (ICM) method. The effects of CFTR modulators on the restoration of the CFTR function were studied in the model of intestinal organoids. To assess the effect of E92K on pre-mRNA splicing, the RT-PCR products obtained from patients’ intestinal organoid cultures were analyzed. Patients with the genetic variant E92K are characterized by an older age of diagnosis compared to homozygotes F508del and a high frequency of pancreatic sufficiency. The results of the sweat test and the ICM method showed partial preservation of the function of the CFTR channel. Functional analysis of CFTR gene expression revealed a weak effect of the E92K variant on mRNA-CFTR splicing. Lumacaftor (VX-809) has been shown to restore CFTR function in an intestinal organoid model, which allows us to consider the E92K variant as a promising target for therapy with CFTR correctors.
Keywords: Bilgisayar Bilimleri; Kimya Mühendisliği ve Teknolojisi; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Spektroskopi; İnorganik Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Computer Sciences; Chemical Engineering and Technology; Life Sciences; Molecular Biology and Genetics; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Spectroscopy; Inorganic Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Bilgisayar Bilimi; Mühendislik; MÜHENDİSLİK, KİMYASAL; KİMYA, İNORGANİK VE NÜKLEER; SPEKTROSKOPİ; KİMYA, FİZİKSEL; KİMYA, ORGANİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); COMPUTER SCIENCE; ENGINEERING; CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; ENGINEERING, CHEMICAL; CHEMISTRY, INORGANIC & NUCLEAR; SPECTROSCOPY; CHEMISTRY, PHYSICAL; CHEMISTRY, ORGANIC; Kataliz; Fizik Bilimleri; Moleküler Biyoloji; Bilgisayar Bilimi Uygulamaları; Fiziksel ve Teorik Kimya; Organik Kimya; İnorganik kimya; Catalysis; Physical Sciences; Molecular Biology; Computer Science Applications; Physical and Theoretical Chemistry; Organic Chemistry; CF Registry; CFTR; cystic fibrosis (CF); E92K; forskolin-induced swelling (FIS) assay; genotype–phenotype correlation; intestinal current measurements (ICM); intestinal organoids; VX-770 potentiator; VX-809 corrector; cystic fibrosis (CF); CFTR; E92K; CF Registry; intestinal current measurements (ICM); intestinal organoids; forskolin-induced swelling (FIS) assay; VX-809 corrector; VX-770 potentiator; genotype–phenotype correlation